Incidence and risk of hypertension associated with PARP inhibitors in cancer patients: a systematic review and meta-analysis - Chen, Xiu; Wen, Qinglian; Kou, Liqiu; Xie, Xiaolu; Li, Jun; Li, Yaling (BMC cancer, 2023)
To analyze the incidence and risk of hypertension associated with poly(adenosine diphosphate-ribose) polymerase (PARP) inhibitors in cancer patients and provide reference for clinicians. We used R software to conduct a meta-analysis of phase II/III randomized controlled trials (RCT) on PARP inhibitors for cancer treatment published in PubMed, Embase, Clinical Trials, Cochrane Library and Web of Science from inception to July 29th, 2022. We included 32 RCTs with 10,654 participants for this meta-analysis. For total PARP inhibitors, the incidence and risk ratio of all-grade hypertension were 12% and 1.22 (95% CI: 0.91-1.65, P = 0.19, I = 81%), and the incidence and risk ratio of grade 3-4 hypertension were 4% and 1.24 (95% CI: 0.74-2.08, P = 0.42, I = 68%). Compared with the control group, the niraparib group, olaparib 800 mg/day group, and olaparib plus cediranib group increased the risk of any grade and grade 3-4 hypertension, while the veliparib group and rucaparib group did not increase the risk of any grade and grade 3-4 hypertension, and olaparib 200 mg-600 mg/day group (exclude olaparib plus cediranib regime) reduced the risk of any grade and grade 3-4 hypertension. Olaparib 200-600 mg/day (excluding olaparib plus cediranib regimen) may be the most suitable PARP inhibitor for cancer patients with high risk of hypertension, followed by veliparib and rucaparib. Niraparib, olaparib 800 mg/day and olaparib combined with cediranib may increase the risk of developing hypertension in cancer patients, clinicians should strengthen the monitoring of blood pressure in cancer patients and give medication in severe cases.